Malcolm Bell iii, The City Plan and Political Agora (Morgantina Studies VII). - Belvedere, Oscar (Journal of Greek Archaeology, 2023)
pp. 444. Wiesbaden: Reichert Verlag, 2022. ISBN 978-3-7520-0021-4 (Print), ISBN 978-3-7520-0131-0 (eBook), hardcover €129.